Strategi Pencegahan Polusi di atas Kapal saat Kebocoran Hydraulic Oil Crane - Hero Budi Santoso; Fahri Effendi (SAINTARA, 2022)
The hydraulic system is a system that utilizes a liquid (oil) as a driving force, therefore the cylinder movement is resulted due to the pressure of the liquid on the cylinder valve so that it can move up and down. In the case of MV. Sinar Bima the ship experienced a crane oil leak which resulted in an oil spill occured on the main deck. Marine Pollution (MARPOL) 73/78 is an International regulation that aims to prevent pollution in the sea caused by ships operation. The aim of this research is to find out how the actions to be taken to prevent an oil pollution, the factors that caused leakage, and the consequences of handling oil spills if not carried out optimally. Data collection methods used are interviews to Senior Officer, observation, and documentation techniques..The data processing technique uses qualitative data analysis by describing the data in the form of an explanation. The results of this study are to optimize and maximize actions to prevent pollution on board and minimize the impact of handling oil spills if not optimally handled. Actions response taken when an oil spill was occured onboard the MV. Sinar Bima.